Analysis of subjective well-being in European Union countries: Group DEA and NPE - Marta Dziechciarz; Maciej Szczeciński (Frontiers in Public Health)
IntroductionThe research aims to analyse the well-being in European Union countries’ identified groups and indicate countries with efficient socio-economic policies. The study explores the differences in households’ subjective well-being in the EU in 2022. The research is a two-pronged examination of selected factors determining well-being in the identified homogeneous groups of EU countries.MethodsThe clustering approach focused on similarities in “inputs and outputs” variables, incorporating key determinants of public health, particularly healthcare system efficiency, social protection policies, and education quality. The evidence-based approaches to health equity and public health assessment include grouping procedures based on variables, which may be defined as “inputs” in social policy and clustering based on variables describing well-being as outcomes in social policy. Furthermore, the efficiency of selected social policy areas in homogenous groups of EU countries was evaluated. The twofold efficiency analysis included Data Envelopment Analysis (DEA) to conduct a deepened study on efficient countries and the Non-Profit Efficiency (NPE) method, both supporting social policy recommendations design aimed at enhancing better health policy outcomes and health-related well-being. It is advisable to compare efficiencies among groups of homogeneous countries. The country’s benchmark should be the DMU, which has similar socio-economic characteristics and health system features. Thus, the classification approach is justified and enables the drawing of much more reliable guidance and the fostering of social policies that contribute to better public health outcomes.Results and discussionThe originality lies in establishing efficiency benchmarks in a two-step analysis involving clustering and efficiency determination with a direct application to developing sustainable social policies. The results of the modified NPE analysis were juxtaposed with benchmarks and targets obtained in DEA, additionally supporting recommendations for improving well-being and social policy effectiveness in the EU.